2020
DOI: 10.33366/bs.v19i2.1744
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Hormon Naa, Pupuk Gandasil Dan Pupuk Growmore Pada Pertumbuhan Tanaman Anggrek

Abstract: Orchid is an ornamental plant, including the Orchidaceae tribe, which is widely favored among the ornamental plant community because it has high economic value, unique shapes, attractive colors and longer-lasting blooming flowers, one of which is a Phalaenopsis orchid. One of the efforts to accelerate the vegetative phalaenopsis can be done with the application of the NAA hormone and leaf fertilizers such as Gandasil fertilizer and Growmore fertilizer. The aims of this research to determine the effect of NAA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Growmore shows the result of an unreal effect on the time of emergence of shoots. This is different from the results of Sumiati's [9] research on orchid plants showing that a dose of 2 gr of Growmore results in a faster bud emergence time. This is because the planted orchid is an acclimatization that is still in the early stages of vegetative growth.…”
Section: Effect Of Growmore Dosage On Growth and Floweringcontrasting
confidence: 93%
See 1 more Smart Citation
“…Growmore shows the result of an unreal effect on the time of emergence of shoots. This is different from the results of Sumiati's [9] research on orchid plants showing that a dose of 2 gr of Growmore results in a faster bud emergence time. This is because the planted orchid is an acclimatization that is still in the early stages of vegetative growth.…”
Section: Effect Of Growmore Dosage On Growth and Floweringcontrasting
confidence: 93%
“…The results of a study conducted by Sulistio et al [8], showed that spraying Growmore at a dose of 4 g / L gave the best results at a flower appearance time of 37 days against the growth of cayenne pepper (Capsicum frutescens L.). The results of a study conducted by Sumiati [9], spraying Growmore at a dose of 2 g / L gave the best results of orchids for a budding time of 35 days.…”
Section: Introductionmentioning
confidence: 99%